NOVELS OF CIVIL LEGISLATION ON LEGAL ENTITIES - D. A. Sumskoy (Гуманитарные и юридические исследования)
The author considers problem of Russian legislation on legal entities. He studies ideas on representation and executive body of the legal entity. Legislative division of legal entities for corporate and unitary, public and non-public, commercial and non-commercial are analyzed. The author deals the essence of the new organizational and legal form of a non-profit organization - Public Law Company.